An Optimal Algorithm for Sales Representative Time Management - Zoltners, Andris A.; Sinha, Prabhakant; Chong, Philip S. C. (Management Science, 1979)
This paper addresses the time management problem confronted by sales representatives. The sales representative planning his itinerary must decide the best way to ration time among the accounts comprising his territory. The time management problem is formulated as an integer program whereby each admissible call frequency for each account is represented by a zero-one decision variable. A branch-and-bound integer programming algorithm for this problem is presented. The algorithm is unique in that two integer programming formulations of the problem are used simultaneously in the search procedure and an approximation-cum-relaxation is evaluated at each branch in the search. Computational testing of the algorithm shows that it can solve many realistic time management problems optimally in fractions of a second.